1993
DOI: 10.1017/s0022215100122571
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss in diabetics

Abstract: The relationship between diabetes and senbsorineural hearing loss has been disputed. This study compares 44 insulin-dependent diabetics with 38 age and sex matched controls. All had pure tone and speech audiometry performed, with any diabetics showing sensorineural deafness undergoing stapedial reflecx decat tests. In 14 diabetics stapedial reflex tests showed no tone decay in any patient, but seven showed evidence of recruitment. Analysis of vaiance showed the diabetics to be significantly deafer than the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
84
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 20 publications
14
84
2
6
Order By: Relevance
“…34 As per the study of Cullen JR and Cinnamond MJ, male patients with diabetes had worse hearing than female patients with diabetes whereas few studies had shown no difference between gender and the severity of deafness. 16 In present study authors report a statistically significant association between diabetes duration and the severity of SNHL, longer the duration higher the grading of deafness particularly among the patients with history of more than 15 years of diabetes the severity of hearing loss was high and most of the studies had also reported the same barring few others. 35,36 Control of blood sugar levels and their association with sensorineural hearing loss has been debated since long and in this study glycosylated haemoglobin was taken into consideration for assessing the diabetes control and we found a statistically significant correlation between the HbA1C levels and the severity of sensorineural hearing loss and our results are in par with the studies done by Cullen R, Kurien M and Tay H L. 16,37,38 …”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…34 As per the study of Cullen JR and Cinnamond MJ, male patients with diabetes had worse hearing than female patients with diabetes whereas few studies had shown no difference between gender and the severity of deafness. 16 In present study authors report a statistically significant association between diabetes duration and the severity of SNHL, longer the duration higher the grading of deafness particularly among the patients with history of more than 15 years of diabetes the severity of hearing loss was high and most of the studies had also reported the same barring few others. 35,36 Control of blood sugar levels and their association with sensorineural hearing loss has been debated since long and in this study glycosylated haemoglobin was taken into consideration for assessing the diabetes control and we found a statistically significant correlation between the HbA1C levels and the severity of sensorineural hearing loss and our results are in par with the studies done by Cullen R, Kurien M and Tay H L. 16,37,38 …”
Section: Discussionsupporting
confidence: 48%
“…Although there is mounting evidence for a relationship between diabetes and hearing impairment the awareness of auditory organ involvement in the course of diabetes is still not widespread among healthcare providers involved in diabetes care. 16 There are a number of physiologically plausible theories about the underlying mechanism responsible for hearing loss occurring with diabetes such as microangiopathic changes involving the coclea, advanced glycation end products leading onto vascular endothelial damage which further leads onto hearing loss, and reactive oxygen species/oxidative stress in basal hair cells leading to hearing loss. 17 As of today only very few Indian studies had been conducted to assess the deafness levels among diabetic patients and so this study was undertaken to assess the hearing loss among the type II diabetes mellitus patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that support the hypothesis that there is possible association between hearing loss and diabetes [1,2,5,8,15], the authors noted the association was predominantly present at higher frequencies. However, these study mention little about the controls and other important factors such as noise exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Since both Type 1 (insulin dependent diabetes mellitus, IDDM) and type 2 (non insulin dependent diabetes mellitus, NIDDM) diabetes are known for their widespread microvascular lesion, their relationship with hearing loss has been widely studied but findings are contradictory. Several studies have reported a positive correlation between diabetes and hearing loss [1,2] others have failed to confirm such association [3,4]. Some investigators have shown that only diabetics with severe peripheral neuropathy or retinopathy are at increased risk of hearing loss [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cullen JR demostró que pacientes diabéticos insulino dependientes eran significativamente más hipoacúsicos que el grupo control 12 . Díaz de León Morales y col encuentran pérdidas auditivas subclínicas en frecuencias agudas y deterioro de la respuesta auditiva del tronco cerebral, pero ésta fue independiente de otras complicaciones de microangiopatía, como retinopatía, neuropatía o nefropatía diabética 13 .…”
Section: Introductionunclassified